The macroeconomic effects of import tariffs in a model with multinational firms and foreign direct investment - Werner Roeger; Paul J. J. Welfens (International Economics and Economic Policy, 2022)
Recent (de-)globalization tendencies and rising protectionist measures has created new interest in studying the effects of unilateral and world-wide tariffs. This paper contributes to this issue by taking into account that international transactions in goods and services increasingly take the form of foreign direct investment. We look at the effects of import tariffs in the context of a two-region DSGE model with both an exporting and an FDI sector. We find that the tariff jumping effect on FDI is largely outweighed by a cost effect if the tariff is imposed on all imports. This holds in the case of both tariffs imposed unilaterally and worldwide import tariffs. Our analysis confirms the aggregate positive welfare effects of a unilateral tariff, but also shows inefficiencies resulting from consumption and production distortions. This leads to lower GDP and real wages through the investment channel. However, governments can generate a tariff jumping effect by exempting imports of multinationals from tariffs. This reduces negative growth effects but also lowers welfare gains since there are less tariff revenues to support consumption. In the case of a world-wide tariff, exempting imports of multinationals reduces negative welfare effects.
Keywords: C6; E1; E24; F13; F21; F23; 330; DSGE; Macroeconomics; Foreign direct investment; Trade; USA; China